Independent colony foundation in Paraponera clavata (Hymenoptera, Formicidae): First workers lay trophic eggs to feed queen’s larvae - Christian Peeters (Sociobiology, 2017)
Paraponera clavata Smith is a large, notorious, and widely distributed ant, yet its colony founding behavior is poorly known. In the laboratory, a dealate queen collected from Peru reared a first generation of ten adult workers over 18 months; eight cocoons and several larvae failed. Food was obtained outside the nest and given to larvae. It took five and six months before the first two workers emerged, and they were smaller than average (i.e.‘nanitic’). At Q+4, trophic eggs were laid by workers and given directly to medium and mature larvae on three occasions. Six workers were dissected immediately after the queen’s death, and five had yolky oocytes in their ovaries. Queen foraging is known from anecdotal field observations, despite the prothorax (and corresponding neck muscles) being smaller than in other poneroid queens.